REVITALISASI KEKUDUSAN DALAM HIDUP PELAYAN KRISTEN - Roy Charly H. P. Sipahutar (Institut Agama Kristen Negeri Tarutung, 2018)
Abstrak This article attempts to discuss issues of importance in the practical struggle of faith of the church today. Holiness became a major theme in this paper that should also be the key to every Christian Minister. With the socio-historical approach then this article tries to see infull what the Bible says about holiness Holiness is not a status quo that makes stagnate and remain silent, but is a to be lived in the life of every Christian minister. Kata Kunci: Holiness, Christian minister, John Wesley